2017
DOI: 10.1055/s-0037-1604064
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Gentamicin for Intractable Ménière's Disease – A Review and Analysis of Audiovestibular Impact

Abstract: Introduction  Intratympanic gentamicin regulates the symptoms in most patients with incapacitating Ménière's disease. The treatment protocols have changed over the years from medical labyrinthectomy to preservation of vestibular function. Objectives  This study aims to review the audiovestibular response related to the effect of the drug in controlling vertigo. Data Synthesis  Articles were identified by means of a search in the PubMed database using the key words Meniere and intratympanic or transtympanic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
0
22
1
1
Order By: Relevance
“…However, both hearing and vertigo outcomes after ITG can vary depending on the dose, titration, number, and frequency of injections, which has contributed to the large variability in outcomes of previous ITG studies. 14,26,27 In our study, 52.0% of patients showed hearing deterioration after ITG, which is higher than previous findings and could be the result of variability in the numbers of injections patients received along with other previously mentioned factors. 14,22,[25][26][27] Of note, in our study, eight out of 27 patients (29.6%) who underwent ITG developed chronic imbalance and unsteadiness after the treatment.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…However, both hearing and vertigo outcomes after ITG can vary depending on the dose, titration, number, and frequency of injections, which has contributed to the large variability in outcomes of previous ITG studies. 14,26,27 In our study, 52.0% of patients showed hearing deterioration after ITG, which is higher than previous findings and could be the result of variability in the numbers of injections patients received along with other previously mentioned factors. 14,22,[25][26][27] Of note, in our study, eight out of 27 patients (29.6%) who underwent ITG developed chronic imbalance and unsteadiness after the treatment.…”
Section: Discussioncontrasting
confidence: 79%
“…9 Two randomized controlled trials have shown a beneficial effect of ITG for MD compared with placebo, and subsequent studies have further validated the effectiveness of ITG. [10][11][12][13][14] Despite its efficacy and less invasive nature (when compared with surgical procedures), ITG can be hazardous to hearing and can have significant long-term vestibular sequelae. While vestibular hair cells are more sensitive to gentamicin than cochlear hair cells, ITG can still lead to cochlear hair cell and spiral ganglion neuron injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that IT gentamicin injections are well tolerated, improve vertigo symptoms, and have a low incidence of severe hearing loss. 17,19,[303][304][305][306][307][308] Caution must be given to patients who have bilateral MD, as chemical ablation carries the risk for significant bilateral vestibular hypofunction and rare hearing loss. Moreover, despite its effectiveness, the vestibular status of the other (noninvolved) ear should be assessed before recommending treatment with gentamicin to avoid potential bilateral hypofunction.…”
Section: Supporting Textmentioning
confidence: 99%
“…[93][94][95] Finally, in case of failure of conservative therapies, intratympanic gentamicin could be proposed to induce a partial chemical labyrinthectomy. 86,[96][97][98][99][100][101][102][103] Several reviews have evaluated the effectiveness of intratympanic therapies, supporting their use in MD. 104,105 -Surgery: This must be considered with caution, since MD may become bilateral after surgery.…”
Section: Treatmentmentioning
confidence: 99%